Pilihan Raya Umum Ke-12 (PRU-12): “tsunami” politik melayu? - Norhayati Mohd Salleh (Penerbit UKM, 2008)
This paper seeks to discuss the twelfth General Election in Malaysia by focusing on the Malay voters. It is divided into five parts. The first part briely discusses the result of the election. The second part looks into the votong pattern. The third part examines the factors behind the pattern. The four part analyszes the impact of the elections on the Malays. The fifth and final part offers suggestions to tackle the situation. This study focuses only on the Peninsular Malaysia because the General Election did not involve state election in Sarawak.